Subtitling Strategies of Indonesian Subtitles Applied in “Wonka” Movie - Gusti Ayu Komang, Putri Kencana Pebi Anitasari; I Made Rajeg; I Nyoman Udayana (Pusat riset dan Inovasi Nasional, 2025)
The advances in the movie industry have led to the rapid rise of streaming platforms, becoming increasingly popular among people. With countries around the world constantly producing movies, subtitles play an essential role in making films more accessible to a broader audience. Subtitling strategies can be defined as a translation practice involving the display of written text, usually at the bottom of the screen, to convey the original dialogues of the speakers and the information contained in the soundtrack. This study uses data from the lk21 website and analyzes it using Gottlieb’s subtitling strategies theory, which consists of ten specific methods for audiovisual translation: Expansion, Paraphrase, Transfer, Imitation, Transcription, Deletion, Dislocation, Condensation, Decimation, and Resignation. A descriptive qualitative approach was adopted in this study with observation, classification, and note-taking of each subtitle, suitable for the research, and describing the subtitling strategies applied in the movie. The findings show that seven strategies were applied in the Indonesian subtitles, namely paraphrase, transfer, condensation, imitation, deletion, dislocation, and expansion. Among them, paraphrase emerged as the most frequently used strategy, likely because figurative or culture-specific expressions in the source text often required adaptation to preserve their meaning for Indonesian viewers. On the other hand, expansion was identified as the least applied strategy, suggesting that the original dialogues rarely demanded additional explanation. Overall, the strategic use of these methods contributed to producing subtitles that were coherent, culturally adapted, and highly accessible to the target audience.